2017
DOI: 10.4045/tidsskr.17.0240
|View full text |Cite
|
Sign up to set email alerts
|

Psykiatriens indre konflikter eksponert

Abstract: Psykiatriens indre konflikter eksponert 421 Diskusjonen om medisinfrie tilbud innen psykisk helsevern handler om hva psykiatri er -og hva det bør vaere.Siden 2010 har flere brukerorganisasjoner arbeidet for å innføre medisinfrie behandlingstilbud innen psykisk helsevern. Helseminister Høie ga i 2015 de regionale helseforetakene frist til 1. juni 2016 med å etablere et slikt tilbud (1). Det er ikke spesifisert hva tilbudet skal bestå i eller hvem det skal gjelde for, men det vil i praksis rette seg mot pasie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…An editorial in the Journal of the Norwegian Medical Association suggested that the demand for MFS might partly stem from the hegemonic position of biomedical interventions combined with limitations in its scientific achievements concerning psychiatric diagnostics and treatment ( 107 ). This prompted response from MFS critics, defending psychiatry's biomedical achievements.…”
Section: Resultsmentioning
confidence: 99%
“…An editorial in the Journal of the Norwegian Medical Association suggested that the demand for MFS might partly stem from the hegemonic position of biomedical interventions combined with limitations in its scientific achievements concerning psychiatric diagnostics and treatment ( 107 ). This prompted response from MFS critics, defending psychiatry's biomedical achievements.…”
Section: Resultsmentioning
confidence: 99%